Effectiveness of a pharmacist-delivered smoking cessation program in the State of Qatar: a randomized controlled trial - Maguy Saffouh El Hajj; Nadir Kheir; Ahmad Mohd Al Mulla; Rula Shami; Nadia Fanous; Ziyad R. Mahfoud (BMC, 2017)
Abstract Background Cigarette smoking is one of the major preventable causes of death and diseases in Qatar. The study objective was to test the effect of a structured smoking cessation program delivered by trained pharmacists on smoking cessation rates in Qatar. Methods A prospective randomized controlled trial was conducted in eight ambulatory pharmacies in Qatar. Eligible participants were smokers 18 years and older who smoked one or more cigarettes daily for 7 days, were motivated to quit, able to communicate in Arabic or English, and attend the program sessions. Intervention group participants met with the pharmacists four times at 2 to 4 week intervals. Participants in the control group received unstructured brief smoking cessation counseling. The primary study outcome was self-reported continuous abstinence at 12 months. Analysis was made utilizing data from only those who responded and also using intent-to-treat principle. A multinomial logistic regression model was fitted to assess the predictors of smoking at 12 months. Analysis was conducted using IBM-SPSS® version 23 and STATA® version 12. Results A total of 314 smokers were randomized into two groups: intervention (n = 167) and control (n = 147). Smoking cessation rates were higher in the intervention group at 12 months; however this difference was not statistically significant (23.9% vs. 16.9% p = 0.257). Similar results were observed but with smaller differences in the intent to treat analysis (12.6% vs. 9.5%, p = 0.391). Nevertheless, the daily number of cigarettes smoked for those who relapsed was significantly lower (by 4.7 and 5.6 cigarettes at 3 and 6 months respectively) in the intervention group as compared to the control group (p = 0.041 and p = 0.018 respectively). At 12 months, the difference was 3.2 cigarettes in favor of the intervention group but was not statistically significant (p = 0.246). Years of smoking and daily number of cigarettes were the only predictors of smoking as opposed to quitting at 12 months (p = 0.005; p = 0.027 respectively). Conclusions There was no statistically significant difference in the smoking cessation rate at 12 months between the groups. However, the smoking cessation program led to higher (albeit non-significant) smoking cessation rates compared with usual care. More research should be conducted to identify factors that might improve abstinence. Trial registration Clinical Trials NCT02123329 . Registration date 20 April 2014